DUST EXPOSURE AND RESPIRATORY HEALTH SYMPTOMS AMONG WORKERS IN SMALL SCALE SUNFLOWER OIL INDUSTRY IN SINGIDA TANZANIA - Buliga, Venance; Rongo, Larama MB; Mamuya, Simon HD (International Journal of Research -GRANTHAALAYAH, 2017)
Background: Small scale sunflower oil industries are industries which extract oil from sunflower seed. Apart from its contribution to the economic development of the nation, during extraction process much dust concentration produced and respiratory symptoms are unknown. The aim of study was to assess dust exposure and associated respiratory health symptoms among small scale sunflower oil industries workers in Singida Tanzania. Methods: A cross sectional study was conducted and 233 participants were interviewed using a modified American Thoracic Society questionnaire to assess the respiratory health symptoms. A Side Kick Casella Pump was used to collect respirable dust from a sub sample of 66 workers from the sieving section. Results: Respirable dust exposure levels for mean, and Geometrical mean was 10.45 mg/m3 (SD 13.90) and GM=5.25 mg/m3 (GSD 0.51) respectively, and 46% of the dust samples (n=66) were above the TLV of 5 mg/m3. Logistic regression analysis between measured dust and respiratory symptoms found to be statistically significant. Higher prevalence of respiratory health symptoms were seen in those with cough (33%), cough with phlegm (46.8%) and wheezy (41.6%). Conclusion: The study concludes that, respiratory symptoms were high and dust exposure was above recommended levels of 5 mg/m3. We recommend use of appropriate RPE.